2022
DOI: 10.3390/su141811272
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of an Explicit Smoothed Particle Finite Element Method on Shallow Vegetated Slope Stability with Different Root Architectures

Abstract: Planting vegetation is an environmentally friendly method for reducing landslides. Current vegetated slope analysis fails to consider the influence of different root architectures, and the accuracy and effectiveness of the numerical simulations need to be improved. In this study, an explicit smoothed particle finite element method (eSPFEM) was used to evaluate slope stability under the influence of vegetation roots. The Mohr–Coulomb constitutive model was extended by incorporating apparent root cohesion into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 80 publications
1
4
0
Order By: Relevance
“…Jia et al employed numerical analysis to reveal that the safety coefficient of slopes was substantially influenced by the plant spacing. The stability of slopes with a plant spacing of 5 m was consistent with that of bare slopes [47]. Temgoua et al observed tree spacing to improve slope stability [34,48].…”
Section: Factors Affecting Slope Stabilitysupporting
confidence: 53%
See 2 more Smart Citations
“…Jia et al employed numerical analysis to reveal that the safety coefficient of slopes was substantially influenced by the plant spacing. The stability of slopes with a plant spacing of 5 m was consistent with that of bare slopes [47]. Temgoua et al observed tree spacing to improve slope stability [34,48].…”
Section: Factors Affecting Slope Stabilitysupporting
confidence: 53%
“…The stability of shallow slopes can be enhanced by planting vegetation, amongst other methods. Slopes with plant roots on their surfaces are more stable than those with root systems at the foot or top of the slope [47]. The reinforcement effect of plant roots improves slope stability and reduces the range of influence of the sliding surface.…”
Section: Factors Affecting Slope Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Although the traditional finite element method (FEM), which deals with small deformation, can describe the initial failure in the surface of the structure well, it may result in large mesh distortion when dealing with large deformations after the initial failure because the aforementioned method lacks stability and accuracy and is limited in terms of solving large deformation problems in geomechanics [13,15]. The large deformation of geomaterials under time-varying loads is a difficult problem in the field of geomechanics due to considerable soil structural deformation, complex contact conditions and nonlinear soil behaviour [16]. Therefore, the development of effective numerical simulation tools will be very helpful in analysing such problems.…”
Section: Numerical Analysis Methods For Large Deformation In Geomecha...mentioning
confidence: 99%
“…The special report by Intergovernmental Panel on Climate Change (IPCC, 2019) has urged policy makers to increase vegetation plantation in order to combat global CO 2 levels [33]. Plant slope protection engineering is an effective and aesthetically pleasing method for safeguarding slopes while also benefiting the environment and economy [34][35][36][37]. Studies have demonstrated that the survival of plants can influence soil water retention and alter the flow of water within soil [38,39].…”
Section: Introductionmentioning
confidence: 99%